2013
DOI: 10.1620/tjem.229.19
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Administration of Human Parathyroid Hormone before Osteosynthesis Stimulates Cancellous Bone Union in Ovariectomized Rats

Abstract: It has been reported that intermittent administration of human parathyroid hormone (h-PTH) promotes bone healing after surgery for osteoporotic fractures. If bone healing is promoted by the administration of h-PTH during pre-operative waiting period, we can prevent prolonged bed rest. Therefore, we evaluated the effects of pre-operative h-PTH treatment on cancellous bone union and its mechanism for fracture healing in ovariectomized rats as a model for osteoporosis. Ovariectomized 7-month-old female Sprague-Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The results of the study supported that PTH therapy promoted fracture healing in gonadectomized osteopenic animals. Later, Nozaka and colleagues and Tsuchie and colleagues reported that PTH therapy exerted its beneficial effects on healing not only in long bone shaft fractures but also in cancellous bone osteotomy in gonadectomized osteopenic animals …”
Section: Resultsmentioning
confidence: 99%
“…The results of the study supported that PTH therapy promoted fracture healing in gonadectomized osteopenic animals. Later, Nozaka and colleagues and Tsuchie and colleagues reported that PTH therapy exerted its beneficial effects on healing not only in long bone shaft fractures but also in cancellous bone osteotomy in gonadectomized osteopenic animals …”
Section: Resultsmentioning
confidence: 99%
“…Currently, the only clinically approved anabolic therapy for the treatment of osteoporosis is teriparatide (Forteo™), which is a recombinant form of parathyroid hormone (PTH). Past studies have shown that intermittent administration of PTH has significant bone anabolic effects on rats and humans [8][9][10]. Unfortunately, treatments with Forteo™ require daily injection and long-term use of PTH has been associated with osteogenic sarcoma in rats [11][12][13], and thus, its use may be limited due to safety concerns.…”
Section: Introductionmentioning
confidence: 99%
“…33 Together with other studies, PTH shows beneficial effects on healing of fractures in the setting of osteoporosis. [34][35][36][37][38][39] Drugs, such as glucocorticoids, can induce a state of osteopenia within the bones. That is to say that steroids increase bone loss by inhibiting osteoblast formation and function, decreasing collagen synthesis, and decreasing intestinal calcium absorption.…”
Section: Impaired Bone Healing Modelmentioning
confidence: 99%